Evaluation Report on Revamped Public Distribution System - Planning Commission (Planning Commission, 1995)
India has, over the years of planned economic development, achieved self-reliance in production of food grains and other consumer goods. However, wide divergence in administrative, social and geographical situations often cause problems for equitable distribution of essential commodities at reasonable prices to the people in various parts of the country. To overcome this problem of distribution of essential commodities the Public Distribution System (PDS) through the institutional network of Fair Price Shops (FPS) was initiated. The scheme has, during the last four decades, made significant impact in distribution of essential commodities to the vulnerable sections of the people both in the urban and rural areas. But occasional evaluation and monitoring of the performance of the scheme has led to the inescapable assessment that certain vulnerable sections of the people with disadvantages of geographical location, low purchasing power, lack of communication etc. are not getting full benefit of the scheme.
Programme Evaluation Organisation Planning Commission Government of India New Delhi